Adhesive for aramid paper and PI film composite material and preparation method thereof
The adhesive for aramid paper and PI film composite materials addresses the high-temperature and oil resistance challenges by using a specific formulation of bisphenol A epoxy resin and phosphate monomer, achieving superior adhesion and resistance properties.
Patent Information
- Application Number
- CN202411389007.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-08
AI Technical Summary
Existing adhesives for aramid paper and PI film composite materials fail to meet the high performance requirements for high-temperature resistance, oil resistance, and moisture-heat aging resistance, particularly in Class C insulation applications.
An adhesive comprising component A, an organic solvent solution of bisphenol A epoxy resin and high molecular weight hydroxy acrylic resin modified by a phosphate monomer, and component B, a liquid anhydride curing agent, with specific ratios and properties, forming a dense coating film that enhances adhesion and resistance through cross-linking.
The adhesive provides excellent adhesion, high electrical stability, and long-term high temperature and oil resistance, meeting the demanding requirements of composite materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to an adhesive for aramid paper and PI film composite material and a preparation method thereof, belonging to the technical field of chemical adhesives. Background Art
[0002] Traditional insulation tape materials usually use materials such as polyvinyl chloride (PVC) or rubber, which are relatively heavy, have poor temperature resistance, general flame retardancy, poor sustainability, and are prone to pollution and harm to the environment and ecosystem. With the expansion of the application range of cables and the improvement of requirements, the development of lightweight high-performance insulation tape materials has become an urgent need. Meta-aramid paper is a high-strength, high-modulus, high-performance material with the characteristics of high temperature resistance, corrosion resistance, flame retardancy, oxidation resistance, and high insulation; polyimide (PI) with a low expansion coefficient has high strength, high dimensional stability and good processability, which meets the development of flexible printed circuits towards high density. Aramid paper and PI are made into composite materials through adhesives. Compared with some traditional insulation materials, it has higher electrical insulation performance, flame retardancy and mechanical strength, can cope with different working environments and application scenarios, and has better environmental performance.
[0003] The insulation materials of traditional motors mainly include pure insulation paper, pure insulation film, and flexible insulation materials composed of multiple layers of insulation paper and insulation film. The heat resistance grades of these insulation materials are divided into Class A (the maximum allowable temperature is at least 105°C, such as traditional kraft paper), Class E (the maximum allowable temperature is at least 120°C, such as the heat-modified cellulose insulation paper TUKPaper developed by Westinghouse Electric Company in the late 1950s), Class B (the maximum allowable temperature is at least 130°C, such as the new high-temperature resistant insulation paper T910 developed by DuPont through a mixed copying process), Class H (the maximum allowable temperature is at least 180°C, such as flexible insulation paper composite materials NHN, NMN, etc.), and Class C (the maximum allowable temperature is at least 220°C, such as DuPont's 410 insulation paper).
[0004] Chinese patent application CN114085639A provides an adhesive for Class C insulating paper composite materials and a preparation method thereof, wherein a curing agent introduces polysilazane resin modified isocyanate; Chinese patent application CN111040670A provides an adhesive and a preparation method thereof, and a PET insulating adhesive containing the same, which adopts a traditional two-component epoxy resin system; Chinese patent CN206558295U discloses a laminated busbar adhesive film structure with stable high-temperature and high-humidity insulation performance, including a double-sided stretched polyester layer, a polyester adhesive layer, a polyester hot-melt adhesive layer and a matte film; Class C insulating paper composite materials have higher high-temperature resistance, oil resistance, and moisture-heat aging resistance, which puts forward higher performance requirements for high-temperature resistance, oil resistance, and moisture-heat aging resistance for the composite adhesive used, and it is difficult for existing adhesives to meet these requirements. Summary of the invention
[0005] The present invention aims at the deficiencies in the prior art and provides an adhesive for aramid paper and PI film composite materials and a preparation method thereof. The adhesive has good adhesion, and the aramid paper and PI film composite materials prepared therefrom have good adhesion, high electrical stability, and excellent long-term high temperature resistance and oil resistance.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: an adhesive for aramid paper and PI film composite materials, the adhesive comprising component A and component B; the component A is an organic solvent solution of bisphenol A epoxy resin and a high molecular weight hydroxy acrylic resin modified by a phosphate monomer, and the component B is a liquid anhydride curing agent; the weight ratio of the component A to the component B is (5-8):1;
[0007] In terms of weight, the component A includes 10-35 parts of (meth)acrylate monomer, 3-8 parts of (meth)acrylic acid, 10-35 parts of styrene, 2-10 parts of hydroxy acrylate, 0.5-3 parts of initiator, 30-40 parts of organic solvent, 5-10 parts of bisphenol A epoxy resin, and 3-8 parts of unsaturated phosphate monomer; and the molar ratio of the (meth)acrylic acid to the bisphenol A epoxy resin is (1.8-2.5):1.
[0008] Further, the rotational viscosity of component A at 25° C. is 500-2000 mPa.s, and the solid content is 50-70%;
[0009] The B component has a rotational viscosity of 50-500 mPa.s at 25° C. and a solid content of 98-100%.
[0010] Furthermore, the molecular weight Mw of the high molecular weight hydroxy acrylic resin in the A component is 30000-50000, the acid value is ≤5 mgKOH / g, the hydroxyl value is 20-50 mgKOH / g, and the glass transition temperature is -10~5°C.
[0011] Furthermore, in terms of weight, the B component includes 90-97 parts of liquid acid anhydride and 3-10 parts of accelerator.
[0012] Preferably, the weight ratio of component A to component B is 6:1.
[0013] Furthermore, the bisphenol A epoxy resin uses a bisphenol A epoxy resin with an epoxy value of 0.2-0.52.
[0014] Preferably, the bisphenol A epoxy resin uses a bisphenol A epoxy resin with an epoxy value of 0.2. The epoxy functional group of the bisphenol A epoxy resin undergoes a ring-opening reaction with methacrylic acid to obtain a hydroxy acrylic resin, which not only introduces epoxy resin into the acrylic resin chain segment, but also provides active polyhydroxy groups, which cross-link with the curing agent anhydride in component B at a certain temperature (curing temperature) to form a dense coating film, so that the composite material of aramid paper and PI film has better water resistance, heat resistance and oil resistance.
[0015] Further, the unsaturated phosphate monomer is at least one of methacryloyloxyethyl phosphate, ethylene glycol methacrylate phosphate, and 2-hydroxyethyl methacrylate phosphate;
[0016] The (meth)acrylate monomer is at least one of methyl (meth)acrylate, butyl (meth)acrylate, ethyl (meth)acrylate, and isobornyl (meth)acrylate;
[0017] The hydroxy acrylate is at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate. The unsaturated phosphate monomer can undergo free radical polymerization with the unsaturated monomer acrylate monomer and styrene to introduce the phosphate into the acrylic resin segment. The unsaturated phosphate can also form chemical bonds with polar groups such as NH bonds of PI film and aramid paper to improve the adhesion between the PI film and aramid paper. In addition, the unsaturated phosphate can also improve the heat resistance and oil resistance of the composite material.
[0018] Preferably, the hydroxy acrylate is hydroxyethyl acrylate.
[0019] Further, the initiator is at least one of azobisisobutyronitrile, azobisisovaleronitrile, tert-butyl hydroperoxide, benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide;
[0020] The organic solvent is at least one of xylene, ethyl acetate, butyl acetate, propylene glycol butyl ether, propylene glycol methyl ether, ethylene glycol methyl ether, and ethylene glycol butyl ether.
[0021] Preferably, the initiator is tert-butyl hydroperoxide.
[0022] Furthermore, the liquid acid anhydride is at least one of methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride;
[0023] The accelerator is at least one of 2-ethyl-4-methylimidazole, imidazole, 1-methylimidazole, and 1-isopropylimidazole.
[0024] Preferably, the accelerator is 2-ethyl-4-methylimidazole.
[0025] The present invention also discloses a method for preparing an adhesive for aramid paper and PI film composite materials, the preparation method comprising:
[0026] Preparation of component A: adding bisphenol A epoxy resin and an organic solvent into a reaction kettle, heating to raise the temperature, then dripping a mixture of (meth)acrylate monomer, (meth)acrylic acid, styrene, hydroxyacrylate, initiator, and unsaturated phosphate monomer into the reaction kettle, keeping the temperature for reaction after the dripping is completed, and cooling to room temperature after the reaction is completed to obtain component A;
[0027] Preparation of component B: liquid acid anhydride and imidazole accelerator, stirring and reacting under heating conditions to obtain component B;
[0028] When the adhesive is used, the component A and the component B are mixed evenly according to the formula ratio and then applied.
[0029] Further, when preparing component A, the heating temperature is 80-130°C, the dripping time of the mixture is 3-8h, and the reaction time is 3-8h;
[0030] When preparing component B, the heating temperature is 75-85°C and the reaction time is 0.5-3h.
[0031] The beneficial effects of the present invention are:
[0032] The adhesive of the composite material of aramid paper and PI film provided by the present invention comprises a main agent (component A) and a curing agent (component B), wherein the main agent adopts component A, which is mainly composed of phosphate monomer, bisphenol A epoxy and acrylic resin; the curing agent adopts a modified acid anhydride curing agent, and after the reaction between the main agent and the curing agent, the aramid paper and the PI film have excellent initial adhesion and final bonding strength. The main agent adopts hydroxyl polyacrylic resin with bisphenol A epoxy resin and phosphate monomer modification, acrylic ester monomer and styrene as main raw materials, and has excellent bonding strength to both aramid paper and PI film; by adding bisphenol A epoxy resin and unsaturated phosphate monomer, the adhesion between PI film and aramid paper can be enhanced, and the oil resistance and water resistance of the adhesive layer at high temperature can be improved. The curing agent adopts anhydride, which has excellent bonding strength to the aramid paper material after cross-linking and curing with the main agent, and has excellent high temperature resistance, oil resistance, corrosion resistance, acid and alkali resistance and other properties. The composite adhesive composed of the main agent and the curing agent is used for composite bonding of aramid paper and PI film composite materials, and can meet the requirements for bonding, high temperature resistance, hydrolysis resistance, alkali resistance, chemical resistance and other properties.
[0033] In the component A of the adhesive of the present invention, there is a synergistic relationship between the bisphenol A epoxy resin, the unsaturated phosphate monomer and the (meth) acrylic acid. Specifically, the unsaturated phosphate reacts with the (meth) acrylic acid to form a main component of the acrylic resin chain segment, and can provide active groups to react with the bisphenol A epoxy resin to form a ring-opening reaction to obtain a polyhydroxy acrylate resin. After these polyhydroxy groups are added to the liquid anhydride curing agent, they are cross-linked under the curing temperature conditions to form a continuous dense film, which has waterproof and oil-resistant properties. In addition, the polar phosphate group can form a chemical bond with the polar groups of the PI film and the aramid paper to improve the interface adhesion. The phosphate itself has heat resistance, which improves the overall heat resistance of the acrylate. In addition, the molar ratio of (meth) acrylic acid to the bisphenol A epoxy resin is (1.8-2.5):1, which is more conducive to improving the performance of the adhesive because the excess polar groups can improve the interface adhesion of the adhesive. DETAILED DESCRIPTION
[0034] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0036] An adhesive for aramid paper and PI film composite materials, the adhesive comprising component A and component B; the component A is an organic solvent solution of bisphenol A epoxy resin and a high molecular weight hydroxy acrylic resin modified by a phosphate monomer, and the component B is a liquid anhydride curing agent; the weight ratio of the component A to the component B is (5-8):1.
[0037] Specifically, the rotational viscosity of component A at 25° C. is 500-2000 mpa.s, and the solid content is 50-70%;
[0038] The B component has a rotational viscosity of 50-500 mPa.s at 25° C. and a solid content of 98-100%.
[0039] Specifically, the high molecular weight hydroxy acrylic resin in component A has a weight average molecular weight of 30,000-50,000, an acid value of ≤5 mgKOH / g, a hydroxyl value of 20-50 mgKOH / g, and a glass transition temperature of -10 to 5°C.
[0040] Specifically, in parts by weight, the component A includes 10-35 parts of (meth)acrylate monomer, 3-8 parts of (meth)acrylic acid, 10-35 parts of styrene, 2-10 parts of hydroxyacrylate, 0.5-3 parts of initiator, 30-40 parts of organic solvent, 5-10 parts of bisphenol A epoxy resin, and 3-8 parts of unsaturated phosphate monomer; and the molar ratio of the (meth)acrylic acid to the bisphenol A epoxy resin is (1.8-2.5):1; wherein the molar number of the bisphenol A epoxy resin is calculated as follows: 100 divided by the epoxy value to obtain the epoxy equivalent, and then the mass of the bisphenol A epoxy resin divided by the epoxy equivalent is the molar number of the bisphenol A epoxy resin.
[0041] The B component includes 90-97 parts of liquid acid anhydride and 3-10 parts of accelerator.
[0042] Specifically, the bisphenol A epoxy resin uses a bisphenol A epoxy resin with an epoxy value of 0.2-0.52.
[0043] Preferably, the bisphenol A epoxy resin is a bisphenol A epoxy resin having an epoxy value of 0.2.
[0044] Specifically, the unsaturated phosphate monomer is at least one of methacryloyloxyethyl phosphate, ethylene glycol methacrylate phosphate, and 2-hydroxyethyl methacrylate phosphate;
[0045] The (meth)acrylate monomer is at least one of methyl (meth)acrylate, butyl (meth)acrylate, ethyl (meth)acrylate, and isobornyl (meth)acrylate;
[0046] The hydroxyacrylate is at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate and hydroxypropyl methacrylate.
[0047] Specifically, the initiator is at least one of azobisisobutyronitrile, azobisisovaleronitrile, tert-butyl hydroperoxide, benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide;
[0048] The organic solvent is at least one of xylene, ethyl acetate, butyl acetate, propylene glycol butyl ether, propylene glycol methyl ether, ethylene glycol methyl ether, and ethylene glycol butyl ether.
[0049] Specifically, the liquid acid anhydride is at least one of methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride;
[0050] The accelerator is at least one of 2-ethyl-4-methylimidazole, imidazole, 1-methylimidazole, and 1-isopropylimidazole.
[0051] A method for preparing an adhesive for a composite material of aramid paper and PI film, the preparation method comprising:
[0052] Preparation of component A: adding bisphenol A epoxy resin and an organic solvent into a reaction kettle, heating to raise the temperature, then dripping a mixture of (meth)acrylate monomer, (meth)acrylic acid, styrene, hydroxyacrylate, initiator, and unsaturated phosphate monomer into the reaction kettle, keeping the temperature for reaction after the dripping is completed, and cooling to room temperature after the reaction is completed to obtain component A;
[0053] Preparation of component B: liquid acid anhydride and imidazole accelerator, stirring and reacting under heating conditions to obtain component B;
[0054] When the adhesive is used, the component A and the component B are mixed evenly according to the formula ratio and then applied.
[0055] Specifically, when preparing component A, the heating temperature is 80-130°C, the dripping time of the mixture is 3-8h, and the reaction time is 3-8h;
[0056] When preparing component B, the heating temperature is 75-85°C and the reaction time is 0.5-3h.
[0057] Example 1
[0058] Preparation of component A: bisphenol A epoxy resin and organic solvent were added to a reaction kettle, heated to 100°C, and then a mixture of (meth)acrylate monomer, (meth)acrylic acid, styrene, hydroxyacrylate, initiator, and unsaturated phosphate monomer was added dropwise to the reaction kettle for 5 hours. After the addition was completed, the mixture was kept warm for 5 hours. After the reaction was completed, the temperature was cooled to room temperature to obtain component A; the molecular weight Mw was 50,000 g / mol, the acid value was 3 mgKOH / g, the hydroxyl value was 25 mgKOH / g, and the glass transition temperature was -3°C; the rotational viscosity at 25°C was 1700 mPa.s, and the solid content was 60%; the composition of component A is shown in Table 1.
[0059] Table 1 Composition of component A in Example 1
[0060]
[0061] Preparation of component B: liquid acid anhydride and imidazole accelerator, stirring and reacting at 80°C for 1.5 hours to obtain component B; the rotational viscosity at 25°C is 300 mPa.s, and the solid content is 99%. The composition of component B is shown in Table 2.
[0062] Table 2 Composition of component B in Example 1
[0063]
[0064] Example 2
[0065] Preparation of component A: Add bisphenol A epoxy resin and organic solvent to a reaction kettle, heat to 80°C, then drop a mixture of (meth)acrylate monomer, (meth)acrylic acid, styrene, hydroxy acrylate, initiator, and unsaturated phosphate monomer into the reaction kettle for 3 hours. After the dropwise addition is complete, heat and react for 8 hours. After the reaction is completed, cool to room temperature to obtain component A; molecular weight Mw is 42500g / mol, acid value is 4mgKOH / g, hydroxyl value is 35mgKOH / g, glass transition temperature is 2°C; rotational viscosity at 25°C is 1900mpa.s, and solid content is 70%. The composition of component A is shown in Table 3.
[0066] Table 3 Composition of component A in Example 2
[0067]
[0068] Preparation of component B: liquid acid anhydride and imidazole accelerator, stirring and reacting at 75°C for 3 hours to obtain component B; the rotational viscosity at 25°C is 380 mPa.s, and the solid content is 98%. The composition of component B is shown in Table 4.
[0069] Table 4 Composition of component B in Example 2
[0070]
[0071] Example 3
[0072] Preparation of component A: Add bisphenol A epoxy resin and organic solvent to a reaction kettle, heat to 130°C, then drop a mixture of (meth)acrylate monomer, (meth)acrylic acid, styrene, hydroxy acrylate, initiator, and unsaturated phosphate monomer into the reaction kettle for 8 hours. After the dropwise addition is complete, heat and react for 3 hours. After the reaction is completed, cool to room temperature to obtain component A; molecular weight Mw is 38000g / mol, acid value is 2mgKOH / g, hydroxyl value is 20mgKOH / g, glass transition temperature is -5°C; rotational viscosity at 25°C is 1400mpa.s, and solid content is 50%. The composition of component A is shown in Table 5.
[0073] Table 5 Composition of component A in Example 3
[0074]
[0075] Preparation of component B: liquid acid anhydride and imidazole accelerator, stirring and reacting at 85°C for 0.5h to obtain component B; the rotational viscosity at 25°C is 420mpa.s, and the solid content is 99%. The composition of component B is shown in Table 6.
[0076] Table 6 Composition of component B in Example 3
[0077]
[0078] Example 4
[0079] Preparation of component A: bisphenol A epoxy resin and organic solvent were added to a reaction kettle, heated to 90°C, and then a mixture of (meth)acrylate monomer, (meth)acrylic acid, styrene, hydroxyacrylate, initiator and unsaturated phosphate monomer was added dropwise to the reaction kettle for 4 hours. After the addition was completed, the mixture was kept warm for 6 hours. After the reaction was completed, the mixture was cooled to room temperature to obtain component A; the molecular weight Mw was 39800 g / mol, the acid value was 3 mgKOH / g, the hydroxyl value was 48 mgKOH / g, and the glass transition temperature was 4°C; the rotational viscosity at 25°C was 900 mPa.s, and the solid content was 70%; the composition of component A is shown in Table 7.
[0080] Table 7 Composition of component A in Example 4
[0081]
[0082] Preparation of component B: liquid acid anhydride and imidazole accelerator, stirring and reacting at 80°C for 1.0h to obtain component B; the rotational viscosity at 25°C is 280mpa.s, and the solid content is 99%. The composition of component B is shown in Table 8.
[0083] Table 8 Composition of component B in Example 4
[0084]
[0085] Comparative Example 1
[0086] The same method as in Example 1 was used to prepare component A and component B, except that when preparing component A, bisphenol A epoxy resin was not added, the molecular weight Mw of component A was 35000 g / mol, the acid value was 5 mgKOH / g, the hydroxyl value was 20 mgKOH / g, and the glass transition temperature was 5° C. The composition of component A in this comparative example 1 is shown in Table 9 below.
[0087] Table 9 Composition of component A in Comparative Example 1
[0088]
[0089] Comparative Example 2
[0090] The same method as in Example 1 was used to prepare component A and component B, except that: when preparing component A, no unsaturated phosphate monomer was added, the molecular weight Mw of component A was 50000 g / mol, the acid value was 4 mgKOH / g, the hydroxyl value was 30 mgKOH / g, and the glass transition temperature was -5°C. The composition of component A in this comparative example 2 is shown in Table 10.
[0091] Table 10 Composition of component A in Comparative Example 2
[0092]
[0093] Comparative Example 3
[0094] The same method as in Example 1 was used to prepare component A and component B, except that (meth)acrylic acid was not added when preparing component A. The composition of component A in this comparative example 3 is shown in Table 11 below.
[0095] Table 11 Composition of component A in Comparative Example 3
[0096]
[0097] Comparative Example 4
[0098] The same method as in Example 1 was used to prepare component A and component B, except that the molar ratio of (meth) acrylic acid to bisphenol A epoxy resin was changed.
[0099] The molar ratio of bisphenol A epoxy resin is 3.3:1 (not within the scope of the present invention). The composition of component A in this comparative example 4 is shown in Table 12 below.
[0100] Table 12 Composition of component A in Comparative Example 4
[0101]
[0102] Comparative Example 5
[0103] The same method as in Example 1 was used to prepare component A and component B, except that the molar ratio of (meth)acrylic acid to bisphenol A epoxy resin was changed. The molar ratio of (meth)acrylic acid to bisphenol A epoxy resin in this comparative example 5 was 1.5:1 (not within the scope of the present invention). The composition of component A in this comparative example 5 is shown in Table 13 below.
[0104] Table 13 Composition of component A in Comparative Example 5
[0105]
[0106] Comparative Example 6
[0107] The same method as in Example 1 was used to prepare component A and component B, except that the curing agent was replaced. In this comparative example 6, the liquid acid anhydride was replaced with another type of MDI curing agent.
[0108] The A component and the B component prepared in each embodiment and comparative example were mixed in a mass ratio of 6:1 and coated between the aramid paper and the PI film, and cured at a curing temperature (80-120°C) to finally prepare a composite material. The aramid paper used was Taihe New Materials Minshida meta-aramid paper yt510, and the PI was a 0.05mm film of KAPTON. The composite material included adhesive and aramid paper on both sides and a PI film in the middle. The prepared composite material was tested for performance. Among them, the peel strength test was referred to GB╱T2792-2014, the heat resistance test was referred to GB T 11021-2007, the oil resistance test was referred to GB / T17948.7-2016, and the breakdown voltage test was referred to GB / T 5591.2-2017. The specific test results are shown in Table 14 below.
[0109] Table 14 Composite material performance test data
[0110]
[0111] It can be seen from the above table data that the adhesives prepared by the preparation method of the present invention in Examples 1-4 have good adhesion, and the composite materials prepared therefrom have good adhesion, high electrical stability, and excellent long-term high temperature resistance and oil resistance.
[0112] From the data comparison between Example 1 and Comparative Example 1, it can be seen that: if epoxy resin is not added to component A, the heat resistance and breakdown voltage resistance of the composite material will be significantly reduced, and the bonding performance will also be reduced; from the data comparison between Example 1 and Comparative Example 2, it can be seen that if unsaturated phosphate monomer is not added to component A, the bonding performance, oil resistance and breakdown voltage resistance of the composite material will all be reduced; from the data comparison between Example 1 and Comparative Example 3, it can be seen that if (meth) acrylic acid is not added to component A, the various properties of the composite material will be reduced. From the data of Example 1 and Comparative Examples 1-3, it can be seen that there is a synergistic relationship between bisphenol A epoxy resin, unsaturated phosphate monomer and (meth) acrylic acid. Specifically, unsaturated phosphate reacts with (meth) acrylic acid by free radicals, and the grafting constitutes the main component of the acrylic resin chain segment, which can provide active groups to react with bisphenol A epoxy resin to form a ring-opening reaction to obtain a polyhydroxy acrylate resin. After these polyhydroxy groups are added to the liquid anhydride curing agent, they are cross-linked under the curing temperature conditions to form a continuous dense film, which has waterproof and oil-resistant properties; in addition, the polar phosphate group can form a chemical bond with the polar groups of the PI film and aramid paper to improve the interfacial adhesion. The phosphate itself has heat resistance, which improves the overall heat resistance of the acrylate. Therefore, adding bisphenol A epoxy resin, unsaturated phosphate monomer and (meth) acrylic acid to the adhesive at the same time is more conducive to obtaining an adhesive with excellent performance.
[0113] From the data comparison of Example 1 and Comparative Examples 4-5, it can be seen that controlling the molar ratio of (meth) acrylic acid and bisphenol A epoxy resin in the formula composition to (1.8-2.5):1 is more conducive to obtaining an adhesive with excellent performance, because excess polar groups can improve the interfacial adhesion of the adhesive.
[0114] From the data comparison of Example 1 and Comparative Example 6, it can be seen that if the curing agent is replaced with MDI isocyanate curing agent, the construction activation period is 5-6h. The glue is prone to gel deterioration over a long period of time because isocyanate NCO has high reaction activity with OH and can react at room temperature, with a short activation period.
[0115] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0116] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. An adhesive for aramid paper and PI film composite material, characterized in that: The adhesive comprises component A and component B; the component A is an organic solvent solution of a bisphenol A epoxy resin and a high molecular weight hydroxy acrylic resin modified by a phosphate monomer, and the component B is a liquid anhydride curing agent; the weight ratio of the component A to the component B is (5-8):1; In terms of weight, the component A comprises 10-35 parts of (meth)acrylate monomer, 3-8 parts of (meth)acrylic acid, 10-35 parts of styrene, 2-10 parts of hydroxy acrylate, 0.5-3 parts of initiator, 30-40 parts of organic solvent, 5-10 parts of bisphenol A epoxy resin, and 3-8 parts of unsaturated phosphate monomer; and the molar ratio of the (meth)acrylic acid to the bisphenol A epoxy resin is (1.8-2.5):1; In terms of weight, the B component includes 90-97 parts of liquid anhydride and 3-10 parts of accelerator; The accelerator is at least one of 2-ethyl-4-methylimidazole, imidazole, 1-methylimidazole, and 1-isopropylimidazole.
2. The adhesive for aramid paper and PI film composite material according to claim 1, characterized in that: The A component has a rotational viscosity of 500-2000 mpa.s at 25°C and a solid content of 50-70%; The B component has a rotational viscosity of 50-500 mpa.s at 25° C. and a solid content of 98-100%.
3. The adhesive for aramid paper and PI film composite material according to claim 1, characterized in that: The molecular weight Mw of the high molecular weight hydroxy acrylic resin in the A component is 30000-50000, the acid value is ≤5 mgKOH / g, the hydroxyl value is 20-50 mgKOH / g, and the glass transition temperature is -10~5°C.
4. The adhesive for aramid paper and PI film composite material according to claim 1, characterized in that: The liquid acid anhydride is at least one of methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride.
5. The adhesive for aramid paper and PI film composite material according to claim 1, characterized in that: The bisphenol A epoxy resin is a bisphenol A epoxy resin with an epoxy value of 0.2-0.
52.
6. The adhesive for aramid paper and PI film composite material according to claim 1, characterized in that: The unsaturated phosphate monomer is at least one of methacryloyloxyethyl phosphate, ethylene glycol methacrylate phosphate, and 2-hydroxyethyl methacrylate phosphate; The (meth)acrylate monomer is at least one of methyl (meth)acrylate, butyl (meth)acrylate, ethyl (meth)acrylate, and isobornyl (meth)acrylate; The hydroxyacrylate is at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate and hydroxypropyl methacrylate.
7. The adhesive for aramid paper and PI film composite material according to claim 1, characterized in that: The initiator is at least one of azobisisobutyronitrile, azobisisovaleronitrile, tert-butyl hydroperoxide, benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide; The organic solvent is at least one of xylene, ethyl acetate, butyl acetate, propylene glycol butyl ether, propylene glycol methyl ether, ethylene glycol methyl ether, and ethylene glycol butyl ether.
8. A method for preparing an adhesive for aramid paper and PI film composite materials according to any one of claims 1 to 7, characterized in that: The preparation method is: Preparation of component A: adding bisphenol A epoxy resin and an organic solvent into a reaction kettle, heating to raise the temperature, then dripping a mixture of (meth)acrylate monomer, (meth)acrylic acid, styrene, hydroxyacrylate, initiator, and unsaturated phosphate monomer into the reaction kettle, keeping the temperature for reaction after the dripping is completed, and cooling to room temperature after the reaction is completed to obtain component A; Preparation of component B: liquid acid anhydride and imidazole accelerator, stirring and reacting under heating conditions to obtain component B; When the adhesive is used, the component A and the component B are mixed evenly according to the formula ratio and then applied.
9. The method for preparing an adhesive for aramid paper and PI film composite material according to claim 8, characterized in that: When preparing component A, the heating temperature is 80-130°C, the dripping time of the mixture is 3-8h, and the reaction time is 3-8h; When preparing component B, the heating temperature is 75-85°C and the reaction time is 0.5-3h.
Citation Information
Cited By
Preparation method of microwave-cured aramid paper high-performance insulating composite material
CN121608462A